Safety and Efficacy of Different Antithrombotic Strategies after Transcatheter Aortic Valve Implantation: A Network Meta-Analysis - Navarese, Eliano Pio; Grisafi, Leonardo; Spinoni, Enrico Guido; Mennuni, Marco Giovanni; Rognoni, Andrea; Ratajczak, Jakub; Podhajski, Przemysław; Koni, Endrin; Kubica, Jacek; Patti, Giuseppe (Thrombosis and Haemostasis, 2021)
Background The optimal pharmacological therapy after transcatheter aortic valve implantation (TAVI) remains uncertain. We compared efficacy and safety of various antiplatelet and anticoagulant approaches after TAVI by a network meta-analysis.Methods A total of 14 studies (both observational and randomized) were considered, with 24,119 patients included. Primary safety endpoint was the incidence of any bleeding complications during follow-up. Secondary safety endpoint was major bleeding. Efficacy endpoints were stroke, myocardial infarction, and cardiovascular mortality. A frequentist network meta-analysis was conducted with a random-effects model. The following strategies were compared: dual antiplatelet therapy (DAPT), single antiplatelet therapy (SAPT), oral anticoagulation (OAC), and OAC + SAPT. The mean follow-up was 15 months.Results In comparison to DAPT, SAPT was associated with a 44% risk reduction of any bleeding (odds ratio [OR]: 0.56 [95% confidence interval, CI: 0.39–0.80]). SAPT was ranked as the safest strategy for the prevention of any bleeding (p-score: 0.704), followed by OAC alone (p-score: 0.476) and DAPT (p-score: 0.437). Consistent results were observed for major bleeding. The incidence of cardiovascular death and secondary ischemic endpoints did not differ among the tested antithrombotic approaches. In patients with indication for long-term anticoagulation, OAC alone showed similar rates of stroke (OR: 0.92 [95% CI: 0.41–2.05], p = 0.83) and reduced occurrence of any bleeding (OR: 0.49 [95% CI: 0.37–0.66], p < 0.01) versus OAC + SAPT.Conclusion The present network meta-analysis supports after TAVI the use of SAPT in patients without indication for OAC and OAC alone in those needing long-term anticoagulation.
Keywords: TAVI; oral anticoagulation; antiplatelet therapy; bleeding events; mortality